2013
DOI: 10.1103/physrevb.88.024410
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature phase diagram of the classical Kitaev-Heisenberg model

Abstract: We investigate the finite-temperature phase diagram of the classical Kitaev-Heisenberg model on the hexagonal lattice. Due to the anisotropy introduced by the Kitaev interaction, the model is magnetically ordered at low temperatures. The ordered phase is stabilized entropically by an order by disorder mechanism where thermal fluctuations of classical spins select collinear magnetic states in which magnetic moments point along one of the cubic directions. We find that there is an intermediate phase between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 37 publications
13
60
0
Order By: Relevance
“…The states which are selected by the thermal fluctuations are the collinear states with the order parameter pointing along one of the cubic axes, thus confirming previous results of the Monte Carlo simulations [34][35][36] and spin wave analysis by Chaloupka et al 23 We discuss the relevance of our findings for the nearest neighbor Kitaev-Heisenberg model for α−RuCl 3 in Sec. IV.…”
Section: Order By Disorder In the Extended Nearest Neighbor Kitaesupporting
confidence: 89%
“…The states which are selected by the thermal fluctuations are the collinear states with the order parameter pointing along one of the cubic axes, thus confirming previous results of the Monte Carlo simulations [34][35][36] and spin wave analysis by Chaloupka et al 23 We discuss the relevance of our findings for the nearest neighbor Kitaev-Heisenberg model for α−RuCl 3 in Sec. IV.…”
Section: Order By Disorder In the Extended Nearest Neighbor Kitaesupporting
confidence: 89%
“…The results in Refs. [20,21] also indicate two thermal transitions upon cooling to any of the ordered low-T phases. The system enters a critical phase at T u , with power-law spin correlations, and a state with true long-range order is reached only below T l < T u .…”
Section: Clean Hk Modelmentioning
confidence: 98%
“…In particular, Price and Perkins found two magnetic transitions in their recent quantum Monte Carlo investigation of classical Kitaev-Heisenberg model. 17,18 They found that in a purely two-dimensional system, the Kitaev term reduces the continuous symmetry due to Heisenberg interaction, and is responsible for finite temperature long range order. In addition, they found that the phase transition proceeds in two steps.…”
mentioning
confidence: 99%